An integrated approach of biomedical image management system - Suhaimi, Mohd Adam; Yasrib, Asma; Rahman, M.M. Hafizur (LAP Lambert Academic Publishing, 2012)
Biomedical images, such as X-ray, CT scan, MRI, etc., are extensively used in diagnosis of diseases, research & teaching in medical science, administration & management of hospital, information for the third party like medico-legal situation & health insurance, and so on. An integrated and efficient biomedical image management system is very essential for the modern healthcare system. In this regard, a prototype system is designed using Java Server Pages in the frontend and MySQL in the backend. And it is applied in three hospitals, named Hospital Tengku Ampuan Afzan, Hospital Selayang, and Hospital Kuala Lumpur. From these three case studies, it is seen that our designed biomedical image management system possesses several attractive features including user friendly, secured and stable, extensible and able to support all image modality, integrated with the hospital information system.